STUDI KOMPARATIF JENIS FONDASI YANG OPTIMAL UNTUK PERENCANAAN GEDUNG REKTORAT UNDARIS DENGAN KONDISI TANAH BERDASARKAN HASIL UJI SONDIR - Muhammad Berry Tan Junior; Muh Alhadad Saputro; Totok Apriyanto; Agung Hari Wibowo (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2025)
Darul Ulum Islamic Centre Sudirman University is planning to add a rectorate building which is expected to support all important activities and events related to the management and development of the university. In this study, the authors identified soil types and compared soil bearing capacity and land subsidence using data from the static cone penetration test (CPT) or sondir test. From the results of the analysis of the bearing capacity and settlement, it was obtained that on a shallow foundation (footplate) with a size of 1,8 x 1,8 m, thickness (hc) 0,4 m, depth 1,5 m, with a bearing capacity of 91,585 ton and settlement of 0,07675 mm in Terzaghi method and 87,110 ton and settlement 0,07671 mm in Meyerhoff method. Meanwhile, for deep foundation (borepile) with a diameter 40 cm and a depth of 9 m, the value of single pile capacity is 25,040 ton, and of the pile group bearing capacity is 75,897 ton and the single pile settlement is 0,06874 cm the pile group settlement is 0,15371 cm in the Meyerhoff method, and for the Schmertman and Nottingham method, the single pile bearing capacity is 23,181 ton and the pile group is 70,264 ton, the single pile settlement is 0,06294 cm and the pile group is 0,14297 cm.